2020
DOI: 10.1016/j.pss.2020.104869
|View full text |Cite
|
Sign up to set email alerts
|

Velocity distribution of larger meteoroids and small asteroids impacting Earth

Abstract: Various meteor and fireball networks exist worldwide. Most data sets which include ground-based observational data of meteors are affected by biases. The larger and faster the entering meteoroid, the brighter is the produced meteor. Hence, small and slow objects often stay undetected. This bias of meteor observations towards faster meteoroids is a challenge if quantitative population and flux models are derived. In this work the velocity distribution of objects in space is analysed by using different data sets… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The velocities in the CNEOS database are not free of errors either. Drolshagen et al (2020) mention that a common velocity error assumed for the CNEOS data is about 1-2 km s −1 , Brown et al (2016) estimated the uncertainty to be in the order of 0.1-0.2 km s −1 , and Devillepoix et al (2019) found for two of ten studied events velocity deviations from independent observations of up to 28%. Furthermore, to calculate the diameter of the impacting object, a spherical shape and a density of 3000 kg m −3 have been assumed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The velocities in the CNEOS database are not free of errors either. Drolshagen et al (2020) mention that a common velocity error assumed for the CNEOS data is about 1-2 km s −1 , Brown et al (2016) estimated the uncertainty to be in the order of 0.1-0.2 km s −1 , and Devillepoix et al (2019) found for two of ten studied events velocity deviations from independent observations of up to 28%. Furthermore, to calculate the diameter of the impacting object, a spherical shape and a density of 3000 kg m −3 have been assumed.…”
Section: Discussionmentioning
confidence: 93%
“…Meteors are caused by small extraterrestrial dust particles, meteoroids, entering the Earth's atmosphere at very high velocities in the range 11.1-73.6 km s −1 (see e.g. Drolshagen et al 2020). Meteors with an absolute magnitude brighter −4 are called fireballs, and the brightest and rarest of which are sometimes referred to as bolides.…”
Section: Introductionmentioning
confidence: 99%
“…The typical velocity uncertainty for meter-scale impactors in the CNEOS catalog was estimated by Brown et al (2016) and Granvik & Brown (2018) to be less than 1 km s −1 , but 2 of 10 events analyzed by Devillepoix et al (2019) have discrepancies with alternate measurements of up to 28% in speed. Drolshagen et al (2020) noted that the CNEOS catalog includes two objects that were detected in space before impact, 2008 TC 3 and 2018 LA, with respective measurement errors of 0.3 and 0.52 km s −1 on the geocentric impact speed. These papers underlined the importance of uncertainties and motivated us to retrieve the measurement uncertainties for the 2014 January 8 meteor specifically.…”
Section: Trajectorymentioning
confidence: 99%
“…For a parabolic trajectory, this mean velocity corresponds to a value of ~13.8 km/s for the velocity of impacting the Earth. Drolshagen et al (2020) noticed that, in the papers they cited, the peak of the distribution of velocities of bodies impacting the Earth was at ~13−15 km/s, while the velocities of meteorites entering the terrestrial atmosphere may change in a range of 11 to 73 km/s, and meteoroids with velocities of 9.8 and 10.9 km/s were also detected. This means that some meteoroids approach the activity sphere of the Earth with almost zero velocity, since the parabolic velocity on the Earth's surface is 11.2 km/s.…”
Section: Probabilities Of Collisions Of Near-earth Objects With the Moonmentioning
confidence: 99%